An Assessment of Project Teacher Exchange for ASEAN Teachers (TEACH) Program - Ma. Lourdes S. Agustin; Darryl Roy Montebon (International Journal of Evaluation and Research in Education (IJERE), 2018)
Association of Southeast Asian Nations (ASEAN) integration aims to unite the South East Asian countries to promote better opportunities for the member countries in different areas such as economics and education. As a response, Philippine Normal University spearheaded the formation of the Association of Southeast Asian Teacher Education Network to promote collaboration with ASEAN countries and enhance teacher education programs. The formation of AsTEN creates the impetus to explore possibilities for the internationalization of teacher education programs among the ASEAN countries. Thus, the Institute of Teaching and Learning of PNU initiated the Project Teacher Exchange for ASEAN Teachers (TEACH). This paper reports the assessment of the piloting of the Project TEACH as experienced by the Thai participants. Moreover, this research aims to develop a model that can be utilized by other ASEAN communities as they prepare for their own international teacher education programs.